Hydrogenation effects on Ni/n-Si (111) Schottky diode characteristics - Sahay P.P.; Srivastava R.S.; Shamsuddin M. (My University, 2025)
Experiments have been performed on Ni/n-Si(lll) Schottky diodes fabricated by the thermal vacuum deposition of nickel on n/n Si epitaxial wafer at ∼10-5 torr pressure. (1-V) and (C-V) characteristics have been measured at different frequencies in the range 10 KHz-1 MHz. Hydrogenation effects on the diode characteristics have been reported from (I-V) and (C-V) studies. It has been found that hydrogen lowers the work function of nickel and also generates the interfacial traps at the Si-SiO2 interface. These results are found in agreement with the results based on transient capacitance response and (C-V) studies. Slight passivation of deep donor states responding the low frequency test signal has also been observed after hydrogenating the diode. Interface states parameters have been extracted from (C-V) characteristics using metal-interfacial layer - semiconductor (MIS) structure moael. © 1992 SPIE. All rights reserved.